Kaitan Potensi Sumber Daya Geologi, dan Gempa Bumi di Daerah Sinabang, Sumatera - Nainggolan, D.A (Pusat Survei Geologi, 2006)
Analysis of Bouguer anomaly data in Sinabang Quadrangle produced a subsurface geological structure model including the configuration of basements of continental and oceanic crusts. Intrepretation of the anomaly patterns, the subsurface profile models including the geological structures depict the geological proseses, tectonics and its relationships with natural resources and tectonic earthquake. The qualitative analyses results of residual and Bouguer anomalies indicate that the structures in the researched area generally have northwest - southeast and southwest - northeast directions. Meanwhile the quantitative analysis shows the presence of two kinds of sedimentary rock with the density of 2.20 gr/cm-3 and 2.35 gr/cm-3 . Keywords : gravity, geological structure, earthquake, Sinabang